Diffusion Distribution Characteristics and Flammable Areas of Refrigerants Encountering Obstacles in Confined Spaces - Li Yalun; Zhou Peixu; Ye Gongran; Zhuang Yuan; Yan Yuhao; Ouyang Hongsheng; Han Xiaohong (Zhileng xuebao)
Refrigerants exhibit different diffusion and distribution characteristics when they encounter obstacles after leaking into confined spaces. The influence of the thermophysical parameters of refrigerants on their diffusion and distribution after encountering obstacles thus needs to be analyzed to facilitate the prediction of flammable areas during the leakage of flammable refrigerant. In this study, R717, R290, R32, and R1234yf were selected. The diffusion and distribution characteristics of the refrigerants encountering high and low obstacles in a confined space were investigated, and the influence of the thermophysical parameters of the refrigerants on the diffusion process and flammable area were analyzed in detail. The results indicated different patterns of rigid collision when the refrigerants encountered a high obstacle after leakage. Refrigerant with lower densities diffused rapidly in the direction opposite to the leakage direction and gathered at the top of the space, whereas refrigerants with higher densities diffused along the surface of the obstacle to the ground. As the height of the measurement point decreased, the mass concentration of R717 decreased from 2.04% to 0.024%, and the mass concentration of R1234yf increased from 0.192% to 1.64%. The mass concentrations of R290 and R744 below the leakage hole were 0.92% and 1.27%, respectively. When the densities of the refrigerants were similar, the refrigerant with a higher viscosity had a higher mass concentration. The flammable area was primarily located above the high obstacle, and as the refrigerant leakage increased, the flammable area in the y-z section of the space gradually extended to the ground. When refrigerants encountered low obstacles after leakage, they accumulated below the leakage hole and gradually diffused to other low mass concentration areas of the space along the surface of the low obstacle. The distribution of refrigerants with lower densities was more uniform. As the densities of refrigerants increased, they accumulated significantly below the leakage hole. As the height of the measurement point decreased, the mass concentrations of R1234yf and R717 increased from 0.066% and 1% to 2.12% and 1.14%, respectively. The flammable area was mainly located in the corner surrounded by the low obstacle and the wall below the leakage hole. With an increase in refrigerant leakage, the flammable area extended to the ground along the surface of the obstacle.